PENATAAN KAWASAN KUMUH DI SEMPADAN SUNGAI PINYUH KABUPATEN MEMPAWAH - Franciscus Xaverius Moan Bura (JURNAL BORNEO AKCAYA, 2022)
ABSTRACT Sungai Pinyuh Village is the most densely populated urban area in Mempawah Regency. The relatively rapid development of urban areas has resulted in urban physical development becoming uncontrollable. This is also experienced in the trade and service sectors, namely the use of space that is not ideal in this urban area. The utilization of river borders in the form of shops is a problem in terms of aesthetics, safety, comfort, and disruption of the function of river borders as protected areas. This study aims to obtain a strategy in dealing with slum areas on the river border. The method used in this research is qualitative-descriptive. Obtaining data by means of observation, interviews, literature studies and related regulations. The method for analyzing the data is qualitative SWOT. The results of this study are that the area is not suitable for settlement or trade and service activities, and it is more recommended to restore its function as a river border protected area.